Estratégias midiáticas na aprendizagem do tema DST/AIDS: ações em rede para reduzir vulnerabilidades de adolescentes e jovens da comunidade de Mãe Luiza, Natal-RN - Furtado, Diolene Borges Machado (2014)
Youngsters and teenagers are still a very vulnerable group of DST/AIDS. In order to combat this vulnerability the community intervention project being developed in Mãe Luiza neighborhood in the city of Natal-RN, entitled Strengthening Community Action Network for Prevention in HIV/AIDS: knowledge and Intervene emerged, popularly known as Project Viva Mãe Luiza. The project develops workshops of educomunication whose approach involves the DST/AIDS subject with the following media: video, photography, and theater playbook. This research integrates the activities of the project and has as main objective to investigate how strategies and practices of media communication developed in Project Viva Mãe Luiza through workshops of educomunication, assisted learning for the prevention of DST/AIDS and contributed to the reduction of vulnerability to DST/AIDS among adolescents and young participants of the project residents of Mãe Luiza community. The methodological basis was based on intervention research, with the technique of gathering daily field data, literature and documentary, in-depth interviews and ethnographic observation. The qualitative analysis was based on the monitoring of video workshops, photography, theater and primer, respectively, crossed by transverse to the prevention of DST/AIDS, conducted between June 2012 and December 2013 issues. Interviews with eight multipliers, aiming to understand their perceptions of vulnerability, prevention, multiplication and use of media that were part of the project were conducted. The analyzes show that learning workshops educomunication community health repercussions both in the development of individual skills in communication as changing perceptions about the vulnerabilities to which they are exposed, the awareness about prevention at the individual and differentiated actions multiplication in the community